La frontière en partage. Conflit, coopération et co-gouvernement entre Luxembourg, Metz et le Barrois (1257–1508) - Dauphant, Léonard (Hémecht. Zeitschrift für Luxemburger Geschichte = Revue d’histoire luxembourgeoise, 2025)
Abstract: „At the end of the Middle Ages, the Duchies of Luxembourg, Bar and Lorraine were part of the Holy Roman Empire. In this area, which can be described as Lotharingian, the powers were not yet states: independent lordships, free cities and principalities coexisted. Borders were simply jurisdictional boundaries, often intertwined. Some territories were jointly administered, such as the Terres communes (‘Common Lands’) between Bar and Luxembourg. Certain powers were shared, such as coining money. The absence of a state also allowed the nobles to manage the public peace themselves and to be involved in cross-border cycles of violence and negotiation. Cross-border cooperation was therefore necessary before the existence of the modern state, which emerged at the same time in the kingdom of France. After the Burgundian Wars (1475–1482), René II of Anjou-Lorraine was the first to attempt to build a state border between his principality and Maximilian of Austria's Duchy of Luxembourg. He outlined territorial control through taxation, the fortification of the frontiers and the fight against smuggling. However, state reforms did not permanently challenge this traditional territoriality, which was based on what Ducan Hardy has termed an “associative political culture”.“
Keywords: Herzogtum Bar; Lothringen

Allégeance et sujétion dans les territoires frontaliers entre Royaume de France et Duché de Luxembourg au 16e siècle. Une histoire «par le bas» de la construction d’une frontière de souveraineté - Gérardin, Emmanuel (Hémecht. Zeitschrift für Luxemburger Geschichte = Revue d’histoire luxembourgeoise, 2025)
Abstract: „During the 16th century, a border of sovereignty was gradually being devised between the Kingdom of France and the Duchy of Luxembourg. At the dawn of modern times, a border was not thought of as a fixed and delimited line but as a moving space, characterized by the entanglement of feudal rights, shaped by the relations between various seigniorial entities. This article reflects on the transformation of feudal structures inherited from the Middle Ages, marked by subjection to local lords, and the gradual emergence of a new conception of sovereignty, territorializing power and asserting state authority over larger spaces. The Duchy of Lorraine and Bar was a buffer state caught up in the confrontation between the Valois and the Habsburgs. It became part of a border march between the Meuse and the Moselle marked out by fortresses: a clear expression of the military front produced by the new balance of power. However, the dynamics of war alone cannot account for the efforts made to stabilize the border. The border was also a space of negotiation around which a princely order emerged. The recognition of a judicial and political concept of sovereignty implied a new relationship between princely power and society, shaped by a new administrative system of controlling a territory and its population. The border came to be redefined as the outward face of a society organized around the sovereignty of the state. Yet this process was far from being achieved at the beginning of the 17th century.“
Keywords: Herzogtum Bar; Lothringen